Balancing Trade-Offs between Policy Responsiveness and Effectiveness: The Impact of Vertical Policy-Process Integration on Policy Accumulation - Christoph Knill; Christina Steinbacher; Yves Steinebach (Public Administration Review, 2021)
In modern democracies, policy stocks pile up over time. In many ways policy accumulation reflects societal modernization and progress. However, if policy accumulation is not matched by corresponding expansions in administrative capacities necessary for policy implementation, a negative trade-off between responsiveness and policy effectiveness evolves. We argue that aligning policy formulation and implementation activities through vertical policy-process integration (VPI) may curb policy accumulation towards a more sustainable level. Our conceptualization of VPI builds upon the distinction of two dimensions: (1) bottom-up integration affecting policy design and improving policies' effectiveness and (2) top-down integration concerning the allocation of implementation costs and, hence, constraining responsiveness incentives. It is the central aim of this viewpoint to raise awareness about the importance of VPI as a potential way out of the responsiveness trap that threatens modern democracies.
Keywords: 340